Effect of hydrogen addition on the laminar burning velocity of n-decane/air mixtures: Experimental and numerical study. (22nd May 2022) - Xu, Cangsu; Wang, Qiyang; Li, Xiaolu; Liu, Kai; Liu, Weinan; Oppong, Francis; Sun, Zuo-Yu
Abstract: Hydrogen is a potential aviation alternative fuel. To explore the influence of hydrogen addition on the combustion of aviation kerosene, the spherical expanding flame method was used to measure the laminar burning velocity and Markstein length of n-decane/hydrogen/air mixtures at 1bar, 2bar and 470 K using experimental and numerical analysis. The experimental LBVs agreed well with the simulation at an initial pressure of 1 bar, but lower than the simulation at 2bar. The laminar burning velocity showed a linear relationship with the hydrogen addition ratio ( R H ) at the different effective fuel-air equivalence ratios ( ϕ F ). The Markstein length decreased with increased R H and initial pressure, hence, increasing the susceptibility of flame front instability. Based on a one-step overall reaction assumption, sensitivity analysis of the premixture mechanism showed that the kinetic effect greatly influenced n-decane/hydrogen/air mixture combustion. Further kinetic analysis indicated that the maximum (H + OH) mole fraction of the chemical reaction is highly responsible for the linear relationship between laminar burning velocity and R H . Highlights: LBV and Markstein length of n-decane/hydrogen/air mixtures were measured. [ X H + X O H ] m a x and LBV had similar linear relationships with the hydrogen addition ratio. Markstein length decreased with increased hydrogen addition ratio and pressure. Sensitivity analysis of the premixture mechanism was investigated.